2001
DOI: 10.1111/j.1349-7006.2001.tb01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free Entry of Human T‐Cell Leukemia Virus Type 1 to Mouse Cells

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) is the etiologic agent for adult T-cell leukemia and HTLV-1-associated myelopathy/tropical spastic paraparesis. Recently we infected newborn mice by inoculating HTLV-1-producing human cells, and found that T-cells, B-cells and granulocytes were infected in vivo. To understand the mechanism of viral-cell interaction and the pathogenesis of HTLV-1 using the mouse model, it is important to clarify the cellular tropism using a cell-free HTLV-1 transmission system. We emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…However, rats and mice are more attractive models for HTLV-1 study because of the ease with which they can be genetically manipulated. HTLV-1 transmission to newborn mice has been reported and the HTLV-1 provirus in mouse spleen has been detected [21]. Nevertheless, no viral expression or antibody production was detected in these mice and, furthermore, mouse cells seem to be less susceptible to HTLV-1 envelope fusion [22,23], even though some conflicting results have been reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, rats and mice are more attractive models for HTLV-1 study because of the ease with which they can be genetically manipulated. HTLV-1 transmission to newborn mice has been reported and the HTLV-1 provirus in mouse spleen has been detected [21]. Nevertheless, no viral expression or antibody production was detected in these mice and, furthermore, mouse cells seem to be less susceptible to HTLV-1 envelope fusion [22,23], even though some conflicting results have been reported [24].…”
Section: Introductionmentioning
confidence: 99%
“…The virus consistently infects rabbits (Akagi et al, 1985;Lairmore et al, 1992), some non-human primates (Nakamura et al, 1987;Murata et al, 1996), and to a lesser extent rats (Suga et al, 1991;Ibrahim et al, 1994). Viral transmission in mice using typical methods of infection produces inconsistent infections and limited virus expression in tissues (Fang et al, 1998;Feng et al, 2001;Furuta et al, 2002a, b;Nitta et al, 2003). Nonhuman primates have been infected with HTLV-1 and certain species have a natural infection with simian T-lymphotropic virus infection type 1 (STLV-1) (Gessain and Dethe 1996;Takemura et al, 2002;Gabet et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, although HTLV-1 consistently infects rabbits [2,3], some non-human primates [4,5], and to a lesser extent, rats [6,7], the virus does not efficiently infect murine cells. Previous studies have indicated that viral transmission in mice, using typical methods of infection, results in inconsistent infections and limited virus expression in tissues [8][9][10].…”
Section: Resultsmentioning
confidence: 99%